Associative Language Represenration of Mental States: Phenomenological Characteristics - Mikhailovna Alekseeva, Ekaterina (2021)
This paper is focused on description of phenomenological characteristics of associative fields of mental states. The method of free association is used in the study. 61 students of both sexes aged 18 to 21 took part in the research. Group 1 had to write down their associations with 25 concepts of mental states. Group 2 participated in an associative experiment: participants had to name orally a single association with each of 25 mentioned mental states. The analysis of associative fields having been reconstructed on the basis of written and oral associations, demonstrated that all of them bear both equal and specific marks. Most of the states under study (as reflection, delight, joy, melancholy, hesitation, fatigue, tranquility) led to written and verbal associations that form the core and perinuclear layers coincided with only few differences, in particular, the forms of their expression. Written and oral associations with individual states (as happiness, love, gaiety, loneliness) could differ significantly from each other. The study reveals the mechanism of formation of specific associations and the characteristics of specific associations based on the concept of mental states. The identification of universal and specific components of the associative representation of states can demonstrate important regularities in shaping the structure of a person's ideas about their inner life.